Pengaruh Latihan Double Leg Speed Hop Dan Squat Jump Terhadap Peningkatan Daya Ledak Otot Tungkai Pemain Sepak Bola Club Salatiga - Rosiyana, Zuamatur; , Sugiono SST.Ft.,M.H. (Kes) (2016)
Background: In the sport of soccer takes peak physical condition to face the competition. During a football game takes the explosive power of the lower body muscles to kick farther, jump higher and run faster. Explosive power leg muscles can be improved with exercises plyometrics speed double leg hop and jump squat is an exercise for the muscles in the limbs. By doing a double leg speed hop and jump squats can increase the explosive power leg muscle. Research Objectives: To determine the effect of exercise speed double leg hop and jump squats, and to know which one is better antra workout speed double leg hop and jump squats to increased leg muscle explosive power of football players club Salatiga. Metoddologi Of Study: The study is a two-group pre-post test design. All subjects were divided into two groups randomly. Statistical analysis using non- parametric tests of hypotheses for <30 ie using Wilcoxon and Mann Whitney. Group I was treated squat jump and the second group was given treatment speed double leg hops. Treatment was given for 4 weeks with a frequency of 3 times per week. Results: In group I (squats jump) results of different test values vertical jump test using Wilcoxon test in the pre - post test result p = 0.07 (p <0.05), which means that there is a difference between the before and after effect jump squat exercises to increase leg muscle explosive power. While group II (double leg speed workout hop) results of different test values vertical jump test using Wilcoxon test in the pre - post test result p = 0.05 (p <0.05), which means that there is a difference between the before and after effects of exercise double leg hops to the increased speed of leg muscle explosive power. At the Mann Whitney test result p = 0.035 (p <0.05), which means there are significant differences in effect between the two groups. Conclusion: Exercise speed double leg hop and jump squats can increase leg muscle explosive power. Exercise double leg hops better speed compared with a jump squat exercises to improve leg muscle explosive power football players.